Analisis Penambahan Teknologi Baterai pada Diesel Electric Multiple Unit (DEMU) - Romal Hadi Setyawan; Muhammad Nizam; Mufti Reza Aulia Putra (Universitas Harapan Medan, 2026)
This study analyzes the impact of integrating a 70 kWh Lithium Titanate Oxide (LTO)-based Battery Energy Storage System (BESS) into the traction system of a Diesel Electric Multiple Unit (DEMU) operating on the Bandung–Cimahi–Padalarang corridor. Two primary problems are addressed: (1) regenerative braking energy wasted as heat in brake resistors, and (2) limited diesel engine power ramp-up response during acceleration. The methodology applies technical analysis based on real operational data loggers at 0.5-second resolution and numerical power flow simulation on a 1,500 VDC link across 12 daily trip cycles. Results show that battery integration increases initial traction effort by 18.1% (82.75 kN → 97.77 kN), reduces 0–25 km/h acceleration time by 26.7% (24.54 s → 17.98 s), and improves notch-P7 acceleration by 39.3%. Fuel savings reach 4.99 liters/cycle (7.14%), equivalent to 21,856 liters/year. Recovered regenerative energy is 6.48 kWh/cycle. CO₂ reductions total 59,228 kg/year, equivalent to planting 2,692 trees. Investment analysis yields a positive NPV of IDR 192,064,475 with a 2.35-year payback period, within the 3.42-year battery service life.